Essential oil extraction from gaharu - Ismail, M. (2007)
Gaharu is one of the most valuable incenses in the world. Gaharu trees form resins that can then produce some of the highest quality gaharu oils. This resinous material, produced by tropical rainforest trees is extremely valuable and has been used for centuries as incense, perfumes, traditional medicine and etc. Currently, other uses of this product are by limited supply and high prices. Due to it rarity and high demand for it, agarwood extract (gaharu oil) bring high prices. The price is around RM 30 000 per liter for lower grade and superior grades could be priced up to RM 60 000 per liter. It is anticipated that the prices of gaharu will remain high in the future because the high demand for gaharu material in Arabic countries, introduction of new applications for gaharu materials in the cosmetical industry and the traditional users of gaharu in China, Japan and India for manufacturaing joss-sticks and other. Given the tremendous demand and diverse applications of gaharu, the economic potential of this product is substantial. Thus, an effective extraction method for recovery the gaharu oil product would be desirable. Currently, the gaharu oil is extracted from the agaharu chips by heating it through hydro distillation process. The drawbacks associated with the hydro distillation method include long hours required to complete the extraction process and produce very low yield. In this research, an enzymatic pretreatment step is introduced in order to speed up the breakage agarwood cell's wall, hence reduce the mass transfer resistances and releases the cell's contents into the extraction medium during the hydro distillation process. Thereby; the oil is released easier in the subsequent separation process. Two process variables, namely extraction time and temperature were varied in order to observe the overall performance of the improved extraction technique and to find the optimum operating condition within the explored range. Similar study was also conducted without enzymatic pretreatment as the basis of comparison for the enzymatic pretreatment hydro distillation. Compared to the conventional method (without enzymatic pretreatment), the improved method (with enzymatic pretreatment) provides high extraction yield (an increase of up to 59%)